A Psychological Aversive Condition Does Not Change Individual Zebrafish Preference For Background Color Or Artificial Plant Enrichments. Issue 4 (2nd October 2022) - Maia, Caroline Marques; Volpato, Gilson Luiz; Braithwaite, Victoria Anne
ABSTRACT: Information on fish preference for environmental conditions can be a useful tool to offer them what they want, an important requirement for welfare purposes. Giving that such an approach deals with psychological states of the fish, we investigated whether psychological stress affects fish preference. In this study, we found that the aversive condition of crossing a white open field did not change individual zebrafish's preference for color background or for plant enrichments, despite a great individual variability of preference response. We conclude that individual preferences for environmental conditions are maintained even following a psychological stressor, and highlight that variability in preference options among individuals raises questions about how to best improve welfare of grouped zebrafish.